THE IMPACT OF GADGET CONSUMPTION PATTERNS ON EARLY CHILDHOOD SOCIAL INTERACTION IN ERA 5.0 - Malikatus Sholihah; Ulya Ainur Rofi'ah; Kholifaharurrohmah Kholifaharurrohmah (Widya Mandala Surabaya Catholic University, 2024)
In the 5.0 era, gadgets are a necessity for everyone, so most parents have introduced gadgets to their children from an early age. As a result, long-term use of gadgets and applications without parental supervision will affect children's social interactions. This research uses qualitative methods with centralized observation and interviews, involving parents as informants. The aim of this research is to determine the impact of gadget consumption patterns on the social interactions of early childhood. Based on the research results, it can be concluded that in the 5.0 era, gadgets have a big influence on the social interaction abilities of young children because young children spend more time playing with gadgets than playing together with their peers.